Division of monomials means product of their quotient of numerical coefficients and quotient of their literal coefficients.
Since, the product of 3m and 5n = 3m × 5n = 15mn; it follows that
(i) \(\frac{15mn}{3m} = \frac{3 \times 5 \times m \times n}{3 \times m}\) = 5n
or, 15mn ÷ 3m = 5n
i.e. when 15mn is divided by 3m, the quotient is 5n.
(ii) \(\frac{15mn}{5n} = \frac{3 \times 5 \times m \times n}{5 \times n}\) = 3m
or, 15mn ÷ 5n = 3m
i.e. when 15mn is divided by 5n, the quotient is 3m.
1. Divide 35mxy
by 5my
35mxy ÷ 5my
= \(\frac{35mxy}{5my}\)
Now, we need to write each term in the expanded form and then cancel the terms which are common to both numerator and denominator.
= \(\frac{\not{5} \times 7 \times \not{m} \times x \times \not{y}}{\not{5} \times \not{m} \times \not{y}}\)
= 7x
= \(\frac{14a^{7}}{2a^{5}}\)
Now, we need to write each term in the expanded form and then cancel the terms which are common to both numerator and denominator.
= \(\frac{\not{2} \times 7 \times \not{a} \times \not{a} \times \not{a} \times \not{a} \times \not{a} \times a \times a}{\not{2} \times \not{a} \times \not{a} \times \not{a} \times \not{a} \times \not{a}}\)
= 7 × a × a= \(\frac{14a^{7}}{2a^{5}}\)
= \(\frac{14}{2} \times \frac{a^{7}}{a^{5}}\)
Now we will write the each numerical part \((\frac{14}{2})\) in the expanded form and then cancel the terms which are common to both numerator and denominator and in case of literal part subtract the smaller power of a literal from bigger power of the same literal.
= \(\frac{\not{2} \times 7}{\not{2}} \times a^{7 - 5}\)
= 7 × ^{2}= \(\frac{81p^{3}q^{6}}{27p^{6}q^{3}}\)
= \(\frac{81}{27} \times \frac{p^{3}q^{6}}{p^{6}q^{3}}\)
Now we will write the each numerical part (\frac{81}{27}) in the expanded form and then cancel the terms which are common to both numerator and denominator and in case of literal part subtract the smaller power of a literal from bigger power of the same literal.
= \(\frac{\not{3} \times \not{3} \times \not{3} \times 3}{\not{3} \times \not{3} \times \not{3}} \times \frac{q^{6 - 3}}{p^{6 - 3}}\)
= \(3 \times \frac{q^{3}}{p^{3}}\)
= \(\frac{3q^{3}}{p^{3}}\)
● Terms of an Algebraic Expression
Types of Algebraic Expressions
Multiplication of Two Monomials
Multiplication of Polynomial by Monomial
Multiplication of two Binomials
Algebra Page
6th Grade Page
From Division of Monomials to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Nov 03, 24 12:50 PM
Oct 29, 24 01:27 PM
Oct 29, 24 12:21 AM
Oct 29, 24 12:06 AM
Oct 28, 24 12:53 AM
● Terms of an Algebraic Expression - Worksheet
Worksheet on Types of Algebraic Expressions
Worksheet on Degree of a Polynomial
Worksheet on Addition of Polynomials
Worksheet on Subtraction of Polynomials
Worksheet on Addition and Subtraction of Polynomials
Worksheet on Adding and Subtracting Polynomials
Worksheet on Multiplying Monomials
Worksheet on Multiplying Monomial and Binomial
Worksheet on Multiplying Monomial and Polynomial
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.